Social Exclusion And The Gender Gap In Education - Lewis, Maureen (The World Bank, 2008)
Despite a sharp increase in the share of girls who enroll in, attend, and complete various levels of schooling, an educational gender gap remains in some countries. This paper argues that one explanation for this gender gap is the degree of social exclusion within these countries, as indicated by ethno-linguistic heterogeneity, which triggers both economic and psycho-social mechanisms to limit girls' schooling. Ethno-linguistic heterogeneity initially was applied to explaining lagging economic growth, but has emerged in the literature more recently to explain both civil conflict and public goods. This paper is a first application of the concept to explain gender gaps in education. The paper discusses the importance of female education for economic and social development, reviews the evidence regarding gender and ethnic differences in schooling, reviews the theoretical perspectives of various social science disciplines that seek to explain such differences, and tests the relevance of ethnic and linguistic heterogeneity in explaining cross-country differences in school attainment and learning. The study indicates that within-country ethnic and linguistic heterogeneity partly explains both national female primary school completion rates and gender differences in these rates, but only explains average national learning outcomes when national income measures are excluded